2004
DOI: 10.1590/s0103-50532004000400022
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-UV and LC-MS analysis of quinonemethides triterpenes in hydroalcoholic extracts of "espinheira santa" (Maytenus aquifolium Martius, Celastraceae) leaves

Abstract: Alguns triterpenos quinonametídicos são conhecidos pela sua citotoxicidade, havendo relatos destas substâncias em várias espécies do gênero Maytenus (Celastraceae), inclusive em Maytenus aquifolium Martius, uma das espécies conhecidas no Brasil como "espinheira santa". Com o objetivo de dispor de um método analítico útil na avaliação da qualidade de medicamentos fitoterápicos de "espinheira santa", foi desenvolvido um procedimento de análise por cromatografia líquida de alta eficiência com detector ultraviolet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
4
0
3
Order By: Relevance
“…Similar results have been reported when using a partition of more polar solvents, such as ethanol, with n ‐hexane or resuspension in n ‐hexane . Some authors have reported the extraction of these compounds with a mixture of n ‐hexane (e.g., ethyl ether (1:1, v/v) or only n ‐hexane) ; however, such extractions are performed through exhaustive maceration or with a Soxhlet apparatus.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Similar results have been reported when using a partition of more polar solvents, such as ethanol, with n ‐hexane or resuspension in n ‐hexane . Some authors have reported the extraction of these compounds with a mixture of n ‐hexane (e.g., ethyl ether (1:1, v/v) or only n ‐hexane) ; however, such extractions are performed through exhaustive maceration or with a Soxhlet apparatus.…”
Section: Resultssupporting
confidence: 67%
“…However, the system exhibits poor selectivity and low chromatographic resolution for pristimerin. Different isocratic systems have been reported in the literature for the elution of QMTs in RP chromatography ; however, the same chromatographic problems, including low selectivity and poor resolution, are observed.…”
Section: Introductionmentioning
confidence: 97%
“…However, we detected pristimerin ( 2 ) and 6-oxopristimerol ( 3 ) in all plant parts of all species studied ( Figure 5 ), including leaves, albeit at a lower concentration than in the roots. Detection of pristimerin ( 2 ) in the hydroalcoholic leaf extract of Maytenus aquifolium has previously been reported [ 19 ]. Salaquinone A and 11 β -hydroxypristimerin were detected in C. cognatum , S. crassifolia and S. elliptica extracts, while vitideasin ( 4 ) was only detected in Salacia extracts ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Os triterpenos das folhas são o friedelan-3-ol e a friedelina. A raiz possui maitenina, pristimerina e os triterpenos quininametídeos (MOSSI et al, 2004;YARIWAKE et al, 2005;NOSSAK et al, 2004). SIQUEIRA et al, 2007;DDINE et al, 2012).…”
Section: Constituintes Quimicos Da Espinheira-santaunclassified